The Impact of Knowledge Management on Organizational Performance through the Balanced Scorecard at Correctional Facilities in Central Java - Mochamad Fitrah Ramadhika; Kusmiyanti Kusmiyanti (Dinasti Publisher, 2025)
Digital-based self-reliance development encourages Correctional Institutions (Lapas) in Central Java to improve organizational effectiveness through the implementation of integrated knowledge management. This study aims to examine the effect of knowledge management on organizational performance by using a balanced scorecard (BSC) approach, especially in supporting prisoner independence programs through digital marketing. Quantitative research methods were applied by distributing questionnaires to 159 staff members from the job training (Bimker) and production activities (Giatja) subsection in 28 correctional institutions in Central Java. Data analysis techniques include validity testing, reliability testing, coefficient of determination, Goodness of Fit model testing, F-Square testing, and path coefficient testing, processed using Smart-PLS version 4.1.1.2. The results showed that knowledge management has a positive and significant effect on organizational performance, with a path coefficient value of 0.857 and a p value of 0.000. R squared value of 0.735 indicates that knowledge management affects organizational performance as measured by the Balanced Scorecard of 73.5%. Each dimension of knowledge creation, adoption, adaptation, and embodiment of knowledge management plays an important role in supporting an organization's internal processes. This study provides empirical insight that strengthening technology-based knowledge management is a fundamental element in creating innovative, productive, and digitally responsive correctional institutions.